2013
DOI: 10.1038/bjc.2013.655
|View full text |Cite
|
Sign up to set email alerts
|

Direct targeting of SUZ12/ROCK2 by miR-200b/c inhibits cholangiocarcinoma tumourigenesis and metastasis

Abstract: Background:The multidrug resistance and distant metastasis of cholangiocarcinoma result in high postoperative recurrence and low long-term survival rates. It has been demonstrated that the ectopic expression of miR-200 suppresses the multidrug resistance and metastasis of cancer. However, the expression and function of miR-200 in cholangiocarcinoma has not yet been described.Methods:In this study, we identified dysregulated microRNAs (miRNAs, miR) in cholangiocarcinoma tissue by microarray analysis, and subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 33 publications
5
77
0
1
Order By: Relevance
“…These contrary findings may be due, in part, to the different source organization and empirical method models. With regard to the role of miR-200c in tumor growth, several recent studies have reported its conflicting roles (23,(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…These contrary findings may be due, in part, to the different source organization and empirical method models. With regard to the role of miR-200c in tumor growth, several recent studies have reported its conflicting roles (23,(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…The miR-200 family is known for their critical roles in the occurrence and progression of many malignant tumors, including HCC, colorectal cancer, and cholangiocarcinoma [44,45]. So we next evaluated whether the association between GIHCG and EZH2 regulates the binding of EZH2 and DNMT1 to the promoter of miR-200b/a/429, or whether GIHCG is required for the binding of EZH2 to the promoter of miR-200b/a/ 429.…”
Section: Gihcg Physically Associates With Ezh2mentioning
confidence: 99%
“…The majority of studies showed that miR-200 family inhibits cell migration and cancer metastasis through targeting epithelial to mesenchymal transition (EMT)-inducing transcription factors zinc-finger E-box-binding homeobox factor 1 (ZEB1) and ZEB2 (9 -11). Fewer studies indicated that miR-200 family may also be capable of inhibiting cell migration and cancer metastasis by targeting other genes such as actin cytoskeleton regulator WAVE3 (Wiskott-Aldrich syndrome protein family member 3), moesin and ROCK2 (Rho-kinase2), or extracellular matrix component fibronectin 1 (13,(35)(36)(37). As summarized in Fig.…”
Section: Discussionmentioning
confidence: 99%